Faktor yang Berhubungan dengan Pemanfaatan Kontrasepsi Pasca Persalinan di Puskesmas Tasinifu Wilayah Perbatasan Indonesia – Timor Leste Tahun 2025 - Clarita de Santalica Ximenes; Frans Geroda Mado; Galuh W. K. D. Larasati; Rina Waty Sirait (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
The use of postpartum contraception (KBPP) is a very important effort to regulate birth spacing, pregnancy spacing, avoid unwanted pregnancies, reduce maternal and infant mortality rates, and improve family welfare. However, the use of KBPP in border areas is still low. This study aims to identify factors associated with the use of postpartum contraception at the Tasinifu Health Center in the border area of Indonesia-Timor Leste in 2025. This study is a quantitative analytical study with a cross-sectional approach. The population in this study consisted of all postpartum mothers in 2024 - June 2025, totaling 190 mothers, and the sample consisted of 64 mothers selected using simple random sampling. The data in this study were analyzed using the Chi-Square statistical test with a significance level of p-value < 0,05. The results of the study showed that there was a relationship between knowledge (p-value = 0,002), husband's support (p-value = 0,000), and perception (p-value = 0,000) with the use of postpartum contraception at the Tasinifu Health Center in the border area of Indonesia-Timor Leste in 2025. The study also showed that there was no relationship between age (p-value = 0,677), parity (p-value = 0,624), and travel distance (p-value = 0,952) with the use of postpartum contraception at the Tasinifu Health Center in the border area of Indonesia-Timor Leste in 2025. Therefore, health workers at the health center are advised to enhance cooperation with village officials in setting targets and motivating the community to use postpartum contraception (KBPP).